A Rogue Doctrine?: The Role of Strategic Culture on US Foreign Policy Behavior. Issue 1 (13th January 2012) - O'Reilly, K. P.
<x xml:space="preserve">Abstract</x> O'Reilly, K. P. (2012) A Rogue Doctrine?: The Role of Strategic Culture on US Foreign Policy Behavior. Foreign Policy Analysis, doi: 10.1111/j.1743‐8594.2011.00171.x To further explore the impact of strategic culture on foreign policy, this article examines the development of the "Rogue Doctrine" within US strategic culture following the Cold War. Critics allege that this doctrine constrains strategic choice resulting in aggressive policies toward alleged rogue states. To assess the impact of this security narrative, the operational codes of two US presidents, William J. Clinton and George W. Bush, are examined. Analysis reveals distinct differences between their perceived interactions with rogue and nonrogue states. The resulting interactions manifest the unique nature of US‐rogue state interactions as these US leaders possess starkly different images of both rogue others as well as self. In the context of dealing with rogue states, these leaders' perceptions of self undergo major transformations indicating tendencies toward more aggressive tactics and the use of force.